The Effectiveness of Reading Challenge Strategy to Improve English Reading Skill(Study at SMA Negeri 11 Sinjai) (Karya Ilmiah Mahasiswa (KIMA), 2026)
This study aims to find out the effectiveness of reading challenge strategy to improve student’ English reading skill and the obstacles in reading English text faced by the student’ at SMA Negeri 11 Sinjai. This study was used quantitative research methods by using pre-experimental design. The population of this study was a student of XI grade SMA Negeri 11  Sinjai consisting of 15 students. The data analysis results showed that the pre-test mean score was 50 and the post-test mean score was 81,3.The study's findings demonstrated that by using Using reading challenges to sharpen your English reading abilities.From the data , showed the students obstacles to the use reading challenge strategy. This research itself had the challenge of students feeling less for improving their reading skills in English where most of them chose to agree (4), neutral (3), and no students chose to very much agree, disagree, very disagreed. From this data we can see that students are assisted with a reading challenge method where students don't choose to disagree and are very disagreed